Chronic Kidney Disease Stage Progression in Liver Transplant Recipients - LaMattina, John C. (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: There is little information on chronic kidney disease (CKD) stage progression rates and outcomes in liver transplant recipients. Identifying modifiable risk factors may help prevent CKD progression in liver transplant recipients. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We performed a retrospective review of 1151 adult, deceased-donor, single-organ primary liver transplants between July 1984 and December 2007 and analyzed kidney outcomes and risk factors for CKD stage progression. Seven hundred twenty-nine patients had an available estimated GFR at 1 year posttransplant to establish a baseline stage. The primary end point was the CKD progression from one stage to a higher stage (lower GFR). RESULTS: Kaplan–Meier estimates of patient survival were 91%, 74%, and 64% at 5, 10, and 15 years, respectively. Estimates of liver allograft survival were 89%, 71%, and 60% at the same time points. At 1 year, 7%, 34%, 56%, 3%, and 1% of patients were in CKD stages 1, 2, 3, 4, and 5. The incidence of stage progression was 28%, 40%, and 53% at 3, 5, and 10 years. The incidence of ESRD was 2.6%, 7.5%, and 18% at 5, 10, and 20 years. Multivariable Cox regression analyses demonstrated that CKD stage at 1 year, pretransplant diabetes and urinary tract infections/hypercholesterolemia in the first year proved to be independent risk factors for stage progression (hazard ratio 1.9, 0.28, 1.39, and 1.46, respectively, P < 0.05). CONCLUSIONS: Future studies will determine whether treatment of risk factors in the first posttransplant year prevent CKD progression in liver transplant recipients.